2010
DOI: 10.1007/s12613-010-0375-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of deterioration in RHA-concrete due to magnesium sulphate attack

Abstract: The assessment of magnesium sulphate attack on concretes containing rice husk ash (RHA, 20wt% of the cementitious materials) with various average particle sizes was investigated. The total cementitious materials were 390 kg and the water-to-binder ratio (W/B) was 0.53 for all mixtures. Specimens were initially cured in water for 7 d and then immersed in the 3wt% magnesium sulphate solution for up to 111 d of exposure. The specimens were subjected to drying-wetting cycles to accelerate sulphate attack. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…At 60 days, BAC with 10% and 15% RHA showed a comparable strength than control BAC, while 20% and 25% RHA showed strength losses of about 15 ) to penetrate BAC and leads to the filling of the porosity of BAC. A similar reflection was also made by Habeeb et al [75]. On the contrary, the loss in the strength of RBAC may be because of the accumulation of magnesium silicate hydrate (M-S-H) gel causing the magnesium to decompose the calcium compounds of C-S-H gel into M-S-H gel, which has no cementitious properties and results in the lowering of compressive strength.…”
Section: Sulfate Attack On Rbacsupporting
confidence: 64%
“…At 60 days, BAC with 10% and 15% RHA showed a comparable strength than control BAC, while 20% and 25% RHA showed strength losses of about 15 ) to penetrate BAC and leads to the filling of the porosity of BAC. A similar reflection was also made by Habeeb et al [75]. On the contrary, the loss in the strength of RBAC may be because of the accumulation of magnesium silicate hydrate (M-S-H) gel causing the magnesium to decompose the calcium compounds of C-S-H gel into M-S-H gel, which has no cementitious properties and results in the lowering of compressive strength.…”
Section: Sulfate Attack On Rbacsupporting
confidence: 64%
“…Chatveera and Lertwattanaruk reported that a replacement level of 30% of RHA-admixed cement mortar showed less expansion when exposed to a high-sulphate environment; however, the expansion of cement mortar increased when increasing the replacement level of RHA, and also reduced the traditional concrete strength [ 110 ]. RHA-blended concrete improved the strength, porosity, and corrosion resistance of concrete as well as resistance to sulphate attack [ 92 , 102 ]. All these results prove beyond doubt that RHA is an effective SCM; at an optimal replacement level up to 30% of Portland cement, RHA improves strength and reduces sulphate reactions, chloride diffusion, and the corrosion rate of embedded steel rebar.…”
Section: Supplementary Cementitious Materials (Scms)mentioning
confidence: 99%
“…The figures show the improvement of the strength immersed in MS relative to the strength of curing with water on all concrete mixed with the SCM products, such as FA, RHA, and GGBS. This can be attributed to the formation of the expansive ettringite in the presence of tricalcium aluminate inside the cement paste matrix and the infiltrated SO 4 + ion, which resulted in filling the voids, thus increasing the concrete maturity [14].…”
Section: Comparing the Effect Of Ms With Curing Condition On Sccmentioning
confidence: 99%